Digestion and Absorption of Milk Phospholipids in Newborns and Adults - Nilsson, Åke; Duan, Rui-Dong; Ohlsson, Lena (Frontiers in Nutrition, 2021)
Milk polar lipids provide choline, ethanolamine, and polyunsaturated fatty acids, which are needed for the growth and plasticity of the tissues in a suckling child. They may also inhibit cholesterol absorption by interacting with cholesterol during micelle formation. They may also have beneficial luminal, mucosal, and metabolic effects in both the neonate and the adult. The milk fat globule membrane contains large proportions of sphingomyelin (SM), phosphatidylcholine (PC), and phosphatidylethanolamine (PE), and some phosphatidylserine (PS), phosphatidylinositol (PI), and glycosphingolipids. Large-scale technical procedures are available for the enrichment of milk fat globule membrane (MFGM) in milk replacement formulations and food additives. Pancreatic phospholipase A2 (PLA2) and mucosal phospholipase B digest glycero-phospholipids in the adult. In the neonate, where these enzymes may be poorly expressed, pancreatic lipase-related protein 2 probably has a more important role. Mucosal alkaline SM-ase and ceramidase catalyze the digestion of SM in both the neonate and the adult. In the mucosa, the sphingosine is converted into sphingosine-1-phosphate, which is both an intermediate in the conversion to palmitic acid and a signaling molecule. This reaction sequence also generates ethanolamine. Here, we summarize the pathways by which digestion and absorption may be linked to the biological effects of milk polar lipids. In addition to the inhibition of cholesterol absorption and the generation of lipid signals in the gut, the utilization of absorbed choline and ethanolamine for mucosal and hepatic phospholipid synthesis and the acylation of absorbed lyso-PC with polyunsaturated fatty acids to chylomicron and mucosal phospholipids are important.